NOCTURNAL POLYURIA IN PARKINSON'S DISEASE PATIENTS PRESENTING WITH NOCTURIA. (29th November 2012) - Smith, MD; Hofereiter, J; Seth, J; Panicker, J
Abstract : Introduction: Nocturia is the commonest non-motor symptom of Parkinson's Disease (PD), having significant impact on sleep and quality of life. The cause for nocturia in PD is poorly understood; this study evaluates factors contributing to nocturia. Methods: This was a cross-sectional survey of consecutive patients with PD referred for nocturia. Information about PD and medications were collected. Factors contributing to nocturia were evaluated, and questionnaires assessing bladder symptoms, quality of life, sleep and a 3 day bladder diary measuring voided volumes were filled. Results: 23 patients participated (mean age 68.5 years, mean duration of PD 10.1 years, mean Hoehn and Yahr staging 3.0). 21 (91.3%) had moderate to severe bladder symptoms and in all, symptoms had a significant impact on quality of life. Bladder diaries revealed that 18 patients (78.3%) had nocturnal polyuria (NP, defined as >33% of urine output at night) (range 17.8–81.1%, mean 46.9%). 8 (34.7%) produced >50% of their urine output at night. Patients with NP more often had longer duration of disease and severity. Of patients with orthostatic hypotension (n=5), four had NP. Patients with NP had less overall fluid intake, increased mean nocturnal voided volume, worse overall bladder symptoms, worse quality of sleep and greater impact on quality of life from bladder symptoms. Conclusion: In this preliminary study, nocturnal polyuria is likely to be an important factor contributing to nocturia in PD.